Review of Advanced Resistance Welding Technologies and Control Methods for Joining State-of-the-Art Materials in Lightweight and Electric Vehicle Manufacturing - Podržaj , Primož; Klobčar , Damjan (Advanced Technologies and Materials, 2025)
Resistance spot welding (RSW) remains a fundamental joining process in modern industrial manufacturing, particularly in the automotive sector. Ensuring consistent weld quality is critical, prompting the development and integration of various monitoring and control systems. This paper reviews the theoretical foundations of RSW and explores diverse control strategies from a control systems perspective. A comprehensive overview of contemporary quality assurance methods—including those leveraging artificial intelligence and machine vision—is provided. The paper also examines the evolving role of RSW in lightweight automotive design and the production of electric vehicles, where diverse materials and dissimilar metal combinations are increasingly common. To address the challenges of welding these advanced materials, state-of-the-art welding and joining technologies are discussed in detail.